City Ordinances of the City of Needles, in The Needles Eye, November 29, 1913, at 3 - (:unkn) unknown (My University, 1913)
Chapter 4, Article 4-Concealed Weapons, §§ 60-61. Approved November 28, 1913. Volume 25, Number 48. (Needles, California): Prohibited concealed carry of pistol, revolver, dirk, derringer, dagger, Bowie-knife, razor, brass knuckles, slung-shot, sand-bag, or other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED